Application of isogeometric method to free vibration of Reissner–Mindlin plates with non-conforming multi-patch. (January 2017) - Zhao, Gang; Du, Xiaoxiao; Wang, Wei; Liu, Bo; Fang, Hongbing
Abstract: The isogeometric method is used to study the free vibration of thick plates based on Mindlin theory. The Non-uniform Rational B-Spline (NURBS) basis functions are employed to build the thick plate's geometry models and serve as the shape functions for solution field approximation in finite element analysis. The Reissner–Mindlin plates built with multiple NURBS patches are investigated, in which several patches of the model have multi-interface and different patches may share a common point. In order to solve the non-conforming interface problems, Nitsche method is employed to glue different NURBS patches and only refers to the coupling conditions in this work. Various plate shapes, different boundary conditions and several kinds of thickness-span ratios are considered to verify the validity of the presented method. The dimensionless frequencies for different cases are obtained by solving the eigenvalue equation problems and compared with the existing reference solutions or the results calculated by ABAQUS software. Several numerical examples exhibit the effectiveness of the isogeometric approach. It shows that the natural frequencies of the Reissner–Mindlin plate can be successfully predicted by the combination of isogeometric analysis and Nitsche method. Highlights: Isogeometric method for free vibration of non-conforming Mindlin plate is proposed. Cases of multi-interface and multi-patches sharing one common point are considered. The mode frequencies of non-conforming Mindlin plate could be predicted. Nitsche based isogeometric method can provide approving convergence.